Design, Modeling, and Control of a Two-Link Robot - Huang, Yushu (2025 International Conference on Mechatronics, Robotics, and Artificial Intelligence (MRAI), 2025)
As a typical simplified model of multi-degree-offreedom robotic systems, the two-link robotic manipulator has significant research value in areas such as kinematic analysis, nonlinear dynamic modeling, and control algorithm validation. This paper establishes both kinematic and dynamic models through kinematic and dynamic analysis. A PID control model for the two-link robot is built in the MATLAB/Simulink simulation environment. By adjusting PID parameters and utilizing the Ziegler-Nichols tuning method, different parameter sets are analyzed and continuously optimized for simulation. The final results confirm that the designed PID control model, with appropriate PID parameters, allows the end-effector trajectory of the two-link robot to closely match the desired trajectory, with an angular displacement error of less than 0.2 %. Subsequently, robustness tests were performed by introducing disturbances to system parameters, and simulations were conducted using the sliding mode control method to compare the performance of different control approaches. The modular simulation system developed in this study provides a scalable technical platform for teaching and experimental research on robotic control algorithms.